Effect of Dietary Graded Levels of Leucaena leucocephala Seeds on Layers Performance, Egg Quality and Blood Parameters - Ahmed, Mohamed Elamin; Abdelati, Khadiga Abbas (International Journal of Poultry Science, 2009)
The layers experiment was conducted to evaluate the effect of different levels of leucaena seed (0, 8, 16 and 24%) on 27 weeks of old laying hens. Parameters studied were egg production, external and internal quality characteristics of eggs, haematological indices and plasma constituents. Feed intake, hen-day egg production, FCR (kg feed/kg egg) and FCR (kg feed/dozens of egg) were depressed with the inclusion of leucaena seeds. Thereafter, birds were placed on control diet for two weeks, which revealed improvement of the performance except for FCR (kg feed/dozens of egg) for birds fed 24% leucaena seeds. Higher egg weight, maximum length and egg shell surface were recorded for birds fed 16% leucaena seeds compared to the others. Maximum width, shell weight and shell% were reduced for birds fed 24% leucaena seeds. Internal quality characteristics of eggs were not significantly affected by the dietary treatments except albumin weight, albumin%, yolk index and yolk color score. Yolk color score consistently increased with the inclusion of leucaena seeds.